(untitled) (International Journal of Physiology, 2019)
Background The purpose of the present study was to observe the effect of urinary bladder distension on cardiovascular reactivity in normal young adults Method Study was conducted in T.M.U Moradabad. Blood pressure and heart rate were recorded in 30 normal healthy young adults of 18–25 years of age group. Parameters were recorded in three stages (phase 1: empty bladder before drinking water, phase 2: after intake of water and with full urinary bladder, phase 3: immediately after emptying of bladder. Results Significant variation (<0.001) in BP and pulse rate in different phases were observed. Systolic BP and diastolic were in First stage 112.2 ± 5.54, 76.73 ± 4.50 Second stage 134.2 ± 4.12, 92.6 ± 3and Third stage 106.6 ± 4.58, 74.4 ± 4.279 respectively. Pulse rates were 70.2 ± 3.07, 78 ± 3.64, 71.8 ± 2.8935 in first, second and third stages respectively and differences were significant(p <0.001). Conclusion Findings suggested that systolic and diastolic blood pressure were raised with full urinary bladder. Conclusion Subjects should be asked to empty bladder before measuring their blood pressure in practice to avoid erroneous recordings.